2023
DOI: 10.1002/gch2.202200183
|View full text |Cite
|
Sign up to set email alerts
|

Assembling the climate story: use of storyline approaches in climate‐related science

Abstract: Storylines are introduced in climate science to provide unity of discourse, integrate the physical and socioeconomic components of phenomena, and make climate evolution more tangible. The use of this concept by multiple scholar communities and the novelty of some of its applications renders the concept ambiguous nonetheless, because the term hides behind a wide range of purposes, understandings, and methodologies. This semi-systematic literature review identifies three approaches that use storylines as a keyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 272 publications
(350 reference statements)
0
2
0
Order By: Relevance
“…We have further identified areas of improvement in the future development of the PCS approach: the way it incorporates the narrative element in different contexts; the way it incorporates value judgments; and finally the way that the evidence chosen to build PCS constrains what is considered plausible. Along with the suggestions of Baulenas et al (2023) to further promote the interaction across different communities using storyline concepts in climate-related research, these areas will help mature the PCS approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further identified areas of improvement in the future development of the PCS approach: the way it incorporates the narrative element in different contexts; the way it incorporates value judgments; and finally the way that the evidence chosen to build PCS constrains what is considered plausible. Along with the suggestions of Baulenas et al (2023) to further promote the interaction across different communities using storyline concepts in climate-related research, these areas will help mature the PCS approach.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives also help identify adaptation pathways in complex human-environmental systems (da Cunha et al, 2020). More recently, Baulenas et al (2023) have explored the use of the storyline concept in climate-related research and have found that PCS is one approach alongside at least two others: discourse analytical approaches, which focus on building narratives that "share meaning [of research objects] among actors, associated practices, and the underlying discourses in relation to climate change, science, and policy" (Baulenas et al, 2023, p. 6), and scenario analysis-which is defined as above. Their analysis suggests that cross-pollination of these approaches can be fruitful.…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, co-production is understood as an "iterative, interactive and collaborative process that brings together a plurality of knowledge sources to mutually define problems and develop usable products to address these problems" (p. 2). The products in this case are the storylines from which the scenario modeling will later on depart (Baulenas et al 2023b). As the interlinkage between climate, energy and society requires considering a diverse range of expertise and perspectives, the preparatory steps before the actual workshop were also a key element of the process.…”
Section: Workhop Methodologymentioning
confidence: 99%
“…Similarly, as the case study was Spain, revising the gray literature from the country helped understand better the context and existing narratives. The gray literature also helped with stakeholder mapping, conducted following the guidelines from Baulenas et al (2023a). The main stakeholder categories were set in the following groups: governmental bodies, resource managers, data-related stakeholders, NGOs, private sector, academia, networks or umbrella organizations, media, and disseminators.…”
Section: Workhop Methodologymentioning
confidence: 99%
See 1 more Smart Citation